Sarcoplasmic Reticulum-Mitochondria Kissing in Cardiomyocytes: Ca2+, ATP, and Undisclosed Secrets - Rossini, Michela; Filadi, Riccardo (Frontiers in Cell and Developmental Biology, 2020)
In cardiomyocytes, to carry out cell contraction, the distribution, morphology and dynamic interaction of different cellular organelles are tightly regulated. For instance, the repetitive close apposition between junctional sarcoplasmic reticulum (jSR) and specialized sarcolemma invaginations, called transverse-tubules (TTs), is essential for an efficient excitation-contraction coupling (ECC). Upon an action potential, Ca2+ microdomains, generated in synchrony at the interface between TTs and jSR, underlie the prompt increase in cytosolic Ca2+ concentration, ultimately responsible for cell contraction during systole. This process requires a considerable amount of energy and the active participation of mitochondria, which encompass ~30% of the cell volume and represent the major source of ATP in the heart. Importantly, in adult cardiomyocytes, mitochondria are distributed in a highly orderly fashion and strategically juxtaposed with SR. By taking advantage of the vicinity to Ca2+ releasing sites, they take up Ca2+ and modulate ATP synthesis according to the specific cardiac workload. Interestingly, with respect to SR, a biased, polarized positioning of mitochondrial Ca2+ uptake/efflux machineries has been reported, hinting the importance of a strictly regulated mitochondrial Ca2+ handling for heart activity. This notion, however, has been questioned by the observation that, in some mouse models, the deficiency of specific molecules, modulating mitochondrial Ca2+ dynamics, triggers non-obvious cardiac phenotypes. This review will briefly summarize the physiological significance of SR-mitochondria apposition in cardiomyocytes, as well as the pathological consequences of an altered organelle communication, focusing on Ca2+ signaling. We will discuss ongoing debates and propose future research directions.